Comparative Proteomic Analysis of Three Xanthomonas spp. Cultured in Minimal and Rich Media. Issue 23 (20th November 2017) - Park, Hye‐Jee; Bae, Nahee; Park, Hanbi; Kim, Dae‐Wi; Han, Sang‐Wook
Abstract: Bacteria change their gene expression when exposed to different nutrient conditions. The levels of proteins do not always correlate with those of RNAs, hence proteomic analysis is required for understanding how bacteria adapt to different conditions. Herein, differentially abundant proteins from Xanthomonas oryzae pv . oryzae (Xoo), X. campestris pv. vesicatoria (Xcv), and X. axonopodis pv. glycines (Xag), which were cultured in rich media and in minimal media, were determined using label‐free shotgun proteomic analysis and clusters of orthologous groups classification. The detected proteins from all three species ranged from 1190 to 1187. Among them, 702, 584, and 529 proteins from Xoo, Xcv, and Xag, respectively, were more (> twofold) abundant depending on the media, indicating that about 11.4–13.8% of proteins from the three species were differentially expressed. The levels of abundant proteins in minimal media were significantly higher than those in rich media for all three species, demonstrating how Xanthomonas species actively change their protein expression in different nutrient conditions. These results will lead to new insights in elucidation of cellular mechanisms involved in virulence and adaption of bacteria to harsh environments for further studies. The MS proteomics data have been deposited to the ProteomeXchange Consortium with the dataset identifier PXD006310.